Alkaloids from the roots of Stemona javanica (Kunth) Engl. (Stemonaceae) and their anti-malarial, acetylcholinesterase inhibitory and cytotoxic activities - Ramli, RA; Pudjiastuti, P; Tjahjandaric, TS; Lie, W; Rattanajak, R; Kamchonwongpaisan, S; Pyne, SG (Elsevier Science Bv, 2024)
Two new protostemonine-type alkaloids, javastemonine A and B (3 and 4) have been isolated from the root extracts of Stemona javanica together with four known Stemona alkaloids, 13-demethoxy-11(S*), 12(R*)-dihydroprotostemonine (1), isoprotostemonine (2), protostemonine and isomaistemonine. The structures and relative configurations of the new alkaloids were determined by spectroscopic analysis. The alkaloids 1 and 2 and protostemonine showed moderated antiplasmodial activities against the Plasmodium falciparum strains, TM4 (IC50 values of 17.7 +/- 3.7, 16.8 +/- 5.4, 16.0 +/- 4.2 mg/mL, respectively) and K1 (IC50 values of 16.8 +/- 3.1, 14.1 +/- 3.7, 11.9 +/- 3.3 mu g/mL, respectively). These compounds showed no significant cytotoxicities against KB or Vero cells or acetylcholinesterase inhibitory activities. (C) 2014 Phytochemical Society of Europe. Published by Elsevier B.V. All rights reserved.